Evaluation of histological damage of solid organs after donor preconditioning with thymoglobulin in an experimental rat model - Cicora, Federico (2013)
Rabbit anti-rat thymoglobulin (rATG) administered to donors with brain death (BD) may improve organs quality. We explored the effects of rATG administered to BD donors in the histology of heart, lungs and small bowel in a rat experimental model. Animals were randomly assigned to 3 groups: V (n = 5) no BD, 2 h ventilation; BD (n = 5) BD and 2 h ventilation; BD and rATG: BD, 2 h ventilation, rATG (10 mg/kg) after BD diagnosis. Histopathological damage scores were based on neutrophil infiltration, airway epithelial cell damage, interstitial edema, hyaline membrane formation, and pulmonary hemorrhage (lungs); neutrophil infiltration and interstitial edema (heart); Park score (bowel). Lung damage was significantly lower in BD + rATG group: V 5 ± 1.6; BD 11.25 ± 0.5, BD + rATG 6.5 ± 1.9 (p < 0.01). Heart: V 2.0 ± 0.81; BD 4.75 ± 1.25 and BD + rATG 3.5 ± 1.7 (p > 0.05). Small bowel: BD 2.25 ± 0.96 vs. BD + rATG 1.00 ± 1.15 (n.s.). Histological damage amelioration in lung and attenuation tendency in heart and small bowel encourages research of cytoprotective strategies to improve organ viability.